A CO-OPERATIVE SETTLEMENT FOR THE UTILIZATION OF THE HERTELENDY CASTLE - Péterfi, Judit (Turisztikai és Vidékfejlesztési Tanulmányok, 2021)
In the successful management of the settlements cooperation, both vertical and horizontal, is indispensable. The present paper introduces such a cooperation which provides a chance through a vertical network to achieve the advantages more effectively. The research presents Kutas as a case study where in the cooperative process a triple unit has been investigated. In favour of the utilisation of the castle allocated in the settlement the paper analyses the structure of the cooperation of the operator, the mayor and the local dwellers. During the impact analysis, which was based on three pillars, field work and interviews played an important part of the primary research. As a result of the analysis of the acquired data the aim of the study is to reveal, analyse and introduce the cooperation trends coming off in the settlement (in favour of the castle). The research uses the empirical data in a way to create the answer for the following question in the end: Is Kutas a cooperative settlement if the future of the castle depends on the efficiency of the cooperation?